Combined Transcript and Metabolite Analysis Reveals Genes Involved in Spider Mite Induced Volatile Formation in Cucumber Plants - Mercke, Per (American Society of Plant Biologists, 2004)
Many plants have an indirect defense against herbivores by emitting volatiles that attract carnivorous enemies of the herbivores. In cucumber (Cucumis sativus) the production of carnivore attractants can be induced by herbivory or jasmonic acid spraying. From the leaves of cucumber plants with and without spider mite infestation, two subtractive cDNA libraries were made that were enriched in cDNA fragments up- or down-regulated by spider mite infestation. A total of 713 randomly selected clones from these libraries were used to make a cDNA microarray. Subsequently, cucumber plants were sprayed with jasmonic acid, mechanically damaged, infested with spider mites, or left untreated (control). Leaf samples were taken at a range of different time points, and induced volatile compounds and mRNA (from the same leaves) were collected. cDNAs prepared from the mRNA were hybridized to the clones on the microarray. The resulting gene expression profiles were analyzed in combination with volatile production data in order to gain insight in the possible involvement of the studied genes in the synthesis of those volatiles. The clones on the microarray and the induced cucumber volatiles could be grouped into a number of clusters in which specific biosynthetic genes clustered with the product of that pathway. For example, lipoxygenase cDNA clones clustered with the volatile (Z)-3-hexenyl acetate and the volatile sesquiterpene (E,E)- α-farnesene clustered with an up-regulated sesquiterpene synthase fragment. This fragment was used to screen a cDNA library which resulted in the cloning of the cucumber (E,E)-α-farnesene and (E)-β-caryophyllene synthases. The use of combined global gene expression analysis and metabolite analysis for the discovery of genes involved in specific biosynthetic processes is discussed.